2016
DOI: 10.14366/usg.15074
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid nodules with isolated macrocalcification: malignancy risk and diagnostic efficacy of fine-needle aspiration and core needle biopsy

Abstract: Purpose:This study was performed to determine the malignancy risk of thyroid nodules with isolated macrocalcification and to evaluate the diagnostic efficacy of fine-needle aspiration (FNA) and core needle biopsy (CNB).Methods:From May 2008 to December 2014, a total of 44 patients with isolated macrocalcifications were enrolled from 4,081 consecutive patients who underwent FNA or CNB at a single institution. We assessed the malignancy risk of nodules with isolated macrocalcification. We compared the diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 17 publications
3
41
1
1
Order By: Relevance
“…Sometimes, the nodule is so hard that the needle may be deflected and damage adjacent structures. Thus, before sampling hard nodules, careful evaluation of the surrounding structures is vital (363753). …”
Section: Devices and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, the nodule is so hard that the needle may be deflected and damage adjacent structures. Thus, before sampling hard nodules, careful evaluation of the surrounding structures is vital (363753). …”
Section: Devices and Proceduresmentioning
confidence: 99%
“…Restriction of free needle movement during FNA may hinder the collection of adequate and accurate cytological specimens from calcified nodules. CNB has a technical failure rate of 1.1% for the collection of tissue from dense calcified thyroid nodules and a non-diagnostic rate of 0.7–7.7% and could prevent unnecessary diagnostic surgery (363753). CNB obtains fewer inconclusive diagnoses than FNA and could minimize the need for diagnostic surgery in patients with calcified thyroid nodules (3653).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…The enrolled patients were selected from 82 patients with isolated macrocalcifications detected by US at two institutions. Forty-four patients with isolated macrocalcifications were found in the cohort data (dataset 1, n=4,081) of patients with thyroid nodules at one institution; details about this cohort have previously been published [6]. Thirtyeight patients with isolated macrocalcifications were found in the cohort data (dataset 2, n=3,061) of patients with thyroid nodules in whom fine-needle aspiration (FNA) or core needle biopsy (CNB) was performed from January 2011 to June 2018 at another institution.…”
Section: Patientsmentioning
confidence: 99%
“…Meanwhile, computed tomography (CT) has the advantage of enabling detailed evaluations of isolated macrocalcifications. A previous study [6] reported that isolated macrocalcifications may present as entirely calcified nodules on CT; however, there has been little research into the CT features of isolated macrocalcifications. Therefore, this study aimed to determine the CT features of thyroid nodules with isolated macrocalcifications detected by US.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation